Pharmacognostical and pharmaceutical analysis of Punarnava guggulu an ayurvedic polyherbal formulation - Kakadiya, Chaitali; Goyal, Mandip; Harisha, C. R.; Shukla, V. J. (International Journal of Advances in Medicine, 2020)
Background: Punarnava Guggulu is a polyherbal formulation mentioned in Bhaishajya Ratnavali containing various Ayurvedic medicinal drugs and specially indicated for the treatment of Amavata and Vatarakta. For assurance of quality of herbal compounds pharmacognostical and pharmaceutical analysis should be done. Methods: Punarnava Guggulu was subjected to microscopic evaluation for Pharmacognostical study, physiochemical analysis like hardness, weight variation, loss on drying, ash value, acid insoluble extract, pH value, water soluble extract, alcohol soluble extract, high performance thin layer chromatography (HPTLC). Results: Pharmacognostical study showed the presence of certain identifying characters of all of the ingredients of Punarnava Guggulu that is Punarnava, Erandamula, Shunthi, Guggulu, Eranda Tail, Trivruta, Danti, Guduchi, Haritaki, Bibhitaki, Amalaki, Maricha, Pippali, Chitraka, Bhallataka and Vidanga. In pharmaceutical study, preliminary physiochemical analysis showed that hardness of the Vati was 4.05 Kg/cm2, ash value 12.84% w/w, acid insoluble ash value 1.56% w/w, loss on drying 1.6% w/w, water soluble extract 35.93% w/w, alcohol soluble extract 22.14% w/w and HPTLC showed 13 spots in 254nm and 8 spots in 366nm. Conclusions: Present work was carried out to standardize the polyherbal formulation Punarnava Guggulu in terms of its identity, quality and purity. Pharmacognostical and physico-chemical observations revealed the specific characters of all active constituents in the preparation were present in it.